Secondary Dean flow characteristics of inelastic Bird-Carreau fluids in curved microchannels - Yoon, Kyu; Jung, Hyun Wook; Chun, Myung-Suk (KOREAN SOC RHEOLOGY, 2020)
To effectively control the mixing of target materials inside microfluidic devices, the Dean flow features of generalized-Newtonian Bird-Carreau (BC) fluids in curved rectangular channels are theoretically investigated, as a passive technique. Governing equations coupled with the Cauchy momentum equation and the BC model are solved using the finite volume scheme with a semi-implicit method for pressure-linked equations-revised (SIMPLER) algorithm. The effects of the rheological parameters of BC model, such as viscosity ratio, power-law index, and relaxation time constant, on the Dean flow are systematically examined in a wide range of Dean numbers (Dn), (very low to O(10(2))). The entire flow characteristics of BC fluids in curved microchannels with increasing Dn are quantified using flow skewness, Dn(Ref)/Dn(MES), and magnitude of vorticity, resulting in two main findings of a more outward-skewed streamwise velocity profile and a more enhanced secondary Dean vortex for non-Newtonian fluids in comparison to the Newtonian case at the same Dn.
Keywords: NON-NEWTONIAN FLUIDS; LAMINAR-FLOW; SEPARATION; PARTICLES